Graphic Design Practices for the Women's Community Nies World Learning House as a Media for Self-Development and Creativity in an Effort for Entrepreneurship - Kezia Noviani Anau; Endang Haryati; Ego S. Sinaga; Humbertus Ngaderman; Benny A. Bungasalu; Yohana Ambokari (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Graphic design is a skill that is much needed today. With the existence of a women's community at the Nies World learning house, it is a good opportunity to open graphic design classes for young women only. Classes will only focus on making desk calendars and wall calendars, both print and digital. The method used is giving lectures related to introductory material and direct practical assistance. Products that were successfully designed by the participants were very good, seen from the type of template chosen, the type of writing, the color of the writing and the selection of images that were appropriate and balanced between existing elements. Some of the best calendars were printed and given back to the participants concerned. With this training, it is hoped that young women can express ideas and be creative in providing their best designs to create quality products. This potential can be beneficial for oneself, as entrepreneurial capital through selling production results or opening design services.